2015
DOI: 10.1007/s11883-015-0556-z
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Obstructive Sleep Apnea and Cardiovascular Disease

Abstract: Obstructive sleep apnea (OSA) is common in the general population and highly prevalent in patients with cardiovascular disease. In this paper, we review (1) the pathophysiological mechanisms of OSA that may causally contribute to cardiovascular disease; (2) current evidence regarding the association between OSA and hypertension, stroke, ischemic heart disease, heart failure, atrial fibrillation, and cardiovascular mortality; and (3) the impact of continuous positive airway pressure (CPAP) treatment on cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 97 publications
0
72
0
6
Order By: Relevance
“…Third, disrupted sleep increases sympathetic nervous activity, leading to an increase in blood pressure and heart rate, which demands cardiac activity at a time when the heart should be regenerating 2, 19, 20. In addition, several studies have shown that SA is associated with hypertension, coronary artery disease, arrhythmias, obesity, diabetes mellitus, and metabolic disturbances, all known to increase the risk of HF 2, 3, 21, 22. Hence, we applied many of these comorbidities in our regression models, including continuous assessment of their presence.…”
Section: Discussionmentioning
confidence: 99%
“…Third, disrupted sleep increases sympathetic nervous activity, leading to an increase in blood pressure and heart rate, which demands cardiac activity at a time when the heart should be regenerating 2, 19, 20. In addition, several studies have shown that SA is associated with hypertension, coronary artery disease, arrhythmias, obesity, diabetes mellitus, and metabolic disturbances, all known to increase the risk of HF 2, 3, 21, 22. Hence, we applied many of these comorbidities in our regression models, including continuous assessment of their presence.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this paper, apparently showing that CPAP had no protective effect against various forms of cardiovascular disease (CVD), came as a surprise to us in light of the accumulated evidence linking OSA with CVD. The currently available data from randomized controlled trials (RCTs) have shown that CPAP has beneficial effects on factors associated with CVD such as blood pressure, increased sympathetic activity, endothelial function, and insulin sensitivity [2,3]. In addition, several observational studies have shown that CPAP use reduces the risk of cardiovascular events due to OSA and cardiovascular related death [2,3].…”
Section: A Paper By Mcevoy Et Al Recently Appeared In the Newmentioning
confidence: 99%
“…The current gold standard treatment for OSAS is CPAP therapy, which has been demonstrated not only to significantly improve sleep quality, reduce the risk of comorbidities and increase patient quality of life, but also to minimize risks of accidents and injuries[71-74]. By effectively diminishing the intermittent hypoxia episodes, CPAP can prevent the activation of pathogenic mechanism that has been shown to affect EPCs number and function.…”
Section: Circulating Stem/progenitor Cellsmentioning
confidence: 99%